2016
DOI: 10.1152/ajplung.00339.2016
|View full text |Cite
|
Sign up to set email alerts
|

Lethal H1N1 influenza A virus infection alters the murine alveolar type II cell surfactant lipidome

Abstract: Alveolar type II (ATII) epithelial cells are the primary site of influenza virus replication in the distal lung. Development of acute respiratory distress syndrome in influenza-infected mice correlates with significant alterations in ATII cell function. However, the impact of infection on ATII cell surfactant lipid metabolism has not been explored. C57BL/6 mice were inoculated intranasally with influenza A/WSN/33 (H1N1) virus (10,000 plaque-forming units/mouse) or mock-infected with virus diluent. ATII cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 59 publications
0
53
0
2
Order By: Relevance
“…For example, infection of mice with the pathogenic PR8 strain of influenza virus (A/Puerto Rico /8/1934 [H1N1]) at a sublethal dose results in spread of the virus to the heart and replication to low levels (9, 10), but the resulting myocarditis is mild and resolves quickly as the virus is cleared (9). Infections with extreme virus doses can cause increased pathogenesis and lethality, but the rapid death induced by such infection regimens might not involve the same pathogenic mechanisms as are initiated during a longer course of infection with a lower dose (14,15). Likewise, animals lacking the type I IFN receptor or downstream signaling molecules experience increased pathogenicity on infection (16,17), but deficiencies in these animals correspond to genetic defects that are rarely seen in humans (18).…”
mentioning
confidence: 99%
“…For example, infection of mice with the pathogenic PR8 strain of influenza virus (A/Puerto Rico /8/1934 [H1N1]) at a sublethal dose results in spread of the virus to the heart and replication to low levels (9, 10), but the resulting myocarditis is mild and resolves quickly as the virus is cleared (9). Infections with extreme virus doses can cause increased pathogenesis and lethality, but the rapid death induced by such infection regimens might not involve the same pathogenic mechanisms as are initiated during a longer course of infection with a lower dose (14,15). Likewise, animals lacking the type I IFN receptor or downstream signaling molecules experience increased pathogenicity on infection (16,17), but deficiencies in these animals correspond to genetic defects that are rarely seen in humans (18).…”
mentioning
confidence: 99%
“…The result suggests that the amount of lamellar body in AT-II cells is not enough to produce a sufficient amount of anti-viral amphisome in vivo. Previous data have shown that IAV infection causes damage to AT-II cells and also significant alterations in surfactant lipid metabolism, such that the levels of major surfactant phospholipids (phosphatidylcholine and phosphatidylglycerol) were reduced while those of minor phospholipids (phosphatidylserine and sphingomyelin) and cholesterol were increased 34 . It is likely that after infection, PVF-tet functions to manage the lipid compartment containing ABCA3, in which cholesterol and sphingolipid are enriched, to be preferentially used to form the anti-viral amphisome that can efficiently isolate HA, although the precise mechanism remains to be clarified.…”
Section: Discussionmentioning
confidence: 95%
“…During the maturation process, one member of the ATPbinding cassette (ABC) transporter family, ABCA3, has an essential role by transporting disaturated phosphatidylcholine, cholesterol, and sphingolipid into the amphisome 32 . Recently, it was reported that in AT-II cells in mice, IAV alters the morphology of the lamellar body to give it a more electron-dense and disrupted structure 33,34 . The involvement of HA in the formation of the altered lamellar body structure and in the pathological role of the amphisome during IAV infection has not been elucidated.…”
mentioning
confidence: 99%
“…For example, infection of mice with the pathogenic PR8 strain of influenza virus (A/Puerto Rico/8/1934 (H1N1)) at a sublethal dose results in spread of the virus to the heart and replication to low levels (Fislova et al, 2009;Kotaka et al, 1990), but the resulting myocarditis is mild and resolves quickly as virus is cleared (Kotaka et al, 1990). Infections with extreme virus doses can cause increased pathogenesis and lethality, but the rapid death that is induced by such infection regimes may not involve the same pathogenic mechanisms that are initiated during a longer course of infection with a lower dose (Vogel et al, 2014;Woods et al, 2016). Likewise, animals lacking the type I interferon (IFN) receptor or downstream signaling molecules experience increased pathogenicity upon infection (Garcia-Sastre et al, 1998;Szretter et al, 2009), but deficiencies in these animals correspond to genetic defects that are rarely seen in humans .…”
Section: Introductionmentioning
confidence: 99%